Arquitetura e luz: o átrio (ex-pátio) - Angelucci, Ornella Maria Castelnuovo (2016)
This study examines the atrium space as part of non-residential buildings for their potential to provide natural light in hot-humid climates. The proposed reading scheme investigates the possibilities of the architect's decisions in relation to its lobby, as well as the use of adjacent elements to forward them to the conditions of each project. A historical summary of the use of such compositional elements in the architecture shows its use for design purpose, climatic and environmental comfort, being performed a review of the design specification for buildings in tropical climates. To study the qualitative aspects of the merger of the atrium throughout the building, it will be taken cases where the central void is markedly expressed.